The eclipsing binary star RZ Cas: accretion-driven variability of the multimode oscillation spectrum. Issue 4 (6th November 2017) - Mkrtichian, D E; Lehmann, H; Rodríguez, E; Olson, E; Kim, S-L; Kusakin, A V; Lee, J W; Youn, J-H; Kwon, S-G; López-González, M J; Janiashvili, E; Tiwari, S K; et al.
Abstract: We analysed photometric time series of the active, semidetached Algol-type system RZ Cas obtained in 1999–2009, in order to search for seasonal and short-term variations in the oscillation spectrum of RZ Cas A. The orbital period shows ±1 s cyclic variations on time-scales of 6–9 years. We detected six low-degree p-mode oscillations with periods between 22.3 and 26.22 min and obtained safe mode identifications using the periodic spatial filter method. The amplitudes and frequencies of all modes vary. We tested and confirm the hypothesis that rapid variations in the pulsation spectrum of the mass-accreting component and rapid increases in the orbital period are driven by high mass transfer and accretion outbursts caused by the cyclic magnetic activity of the Roche lobe-filling donor star. Two rapid pulsation-amplitude decays observed in 2001 and 2009 can be explained by high-mass transfer events separated by the duration of the last 9-yr long magnetic cycle. We also tested and confirm the hypothesis of an acceleration of the outer envelope of the pulsating component. We discovered synchronous, modal m -dependent variations in the frequencies of three identified modes, in good agreement with results of our mode identification using the periodic spatial filter method. We suggest that m -dependent pulsation frequency variations are caused via the Doppler-effect by variations of the rotation speed of the outer envelope of the pulsating gainer. With this method, we obtained the first asteroseismic detection and accurate measurement of the accretion driven acceleration of the outer envelope of the mass-accreting component of an Algol-type star.